Identification of key genes underlying radiosensitivity and radioresistance in endometrial cancer through integrated bioinformatics analysis - Chunhui Wan; Lei Zhang; Ting Yu; Hui Lu; Han Xiao; Juan Du (Frontiers in Genetics)
IntroductionRadiation therapy is crucial in the treatment of endometrial cancer (UCEC). Patients exhibit significant variability in radiosensitivity, affecting therapeutic effect. Scarcity of studies exploring the gene-radiosensitivity relationship based on clinical data. Underlying molecular mechanisms of radiosensitivity and radioresistance require further investigation.MethodsStudy aimed to reveal molecular mechanisms underlying radiosensitivity and radioresistance in UCEC patients. Included 12 radiosensitive and 20 radioresistant UCEC samples. Conducted differential expression analysis to screen for significantly different genes between groups. Applied Lasso regression and randomized survival forest model to identify key genes. Performed functional annotation, correlation analysis, and survival analysis on key genes.ResultsKey genes positively correlated with UCEC tumorigenesis-related genes in the radioresistant group. Reduction in the proportion of Macrophages.M0 observed in the radioresistant group, associated with poor prognosis. GO and GSVA analyses revealed biological processes and signaling pathways involved in key genes. High expression of MARCKS, MACC1, and GRB10 correlated with poorer survival rates. High expression of NINJ2 correlated with higher survival rates and higher sensitivity to radiation therapy.DiscussionStudy contributes to a deeper understanding of UCEC radiosensitivity. Provides theoretical support for the development of personalized radiotherapy regimens in clinical practice. Potential to improve prognosis and quality of life of patients.